Prevention of esophageal strictures after endoscopic submucosal dissection - Kobayashi, Shinichiro (World J Gastroenterol, 2014)
Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) have recently been accepted as less invasive methods for treating patients with early esophageal cancers such as squamous cell carcinoma and dysplasia of Barrett’s esophagus. However, the large defects in the esophageal mucosa often cause severe esophageal strictures, which dramatically reduce the patient’s quality of life. Although preventive endoscopic balloon dilatation can reduce dysphagia and the frequency of dilatation, other approaches are necessary to prevent esophageal strictures after ESD. This review describes several strategies for preventing esophageal strictures after ESD, with a particular focus on anti-inflammatory and tissue engineering approaches. The local injection of triamcinolone acetonide and other systemic steroid therapies are frequently used to prevent esophageal strictures after ESD. Tissue engineering approaches for preventing esophageal strictures have recently been applied in basic research studies. Scaffolds with temporary stents have been applied in five cases, and this technique has been shown to be safe and is anticipated to prevent esophageal strictures. Fabricated autologous oral mucosal epithelial cell sheets to cover the defective mucosa similarly to how commercially available skin products fabricated from epidermal cells are used for skin defects or in cases of intractable ulcers. Fabricated autologous oral-mucosal-epithelial cell sheets have already been shown to be safe.